Cardiac resynchronization therapy in adults with congenital heart disease. Issue 2 (20th January 2017) - Koyak, Zeliha; de Groot, Joris R; Krimly, Ahmed; Mackay, Tara M; Bouma, Berto J; Silversides, Candice K; Oechslin, Erwin N; Hoke, Ulas; van Erven, Lieselot; Budts, Werner; Van Gelder, Isabelle C; Mulder, Barbara J M; et al.
Abstract: Aims: In adults with congenital heart disease (CHD) heart failure is one of the leading causes of morbidity and mortality but experience with and reported outcome of cardiac resynchronization therapy (CRT) is limited. We investigated the efficacy of CRT in adults with CHD. Methods and results: This was a retrospective study including 48 adults with CHD who received CRT since 2003 in four tertiary referral centres. Responders were defined as patients who showed improvement in NYHA functional class and/or systemic ventricular ejection fraction by at least one category. Ventricular function was assessed by echocardiography and graded on a four point ordinal scale. Median age at CRT was 47 years (range 18–74 years) and 77% was male. Cardiac diagnosis included tetralogy of Fallot in 29%, (congenitally corrected) transposition of great arteries in 23%, septal defects in 25%, left sided lesions in 21%, and Marfan syndrome in 2% of the patients. The median follow-up duration after CRT was 2.6 years (range 0.1–8.8). Overall, 37 out of 48 patients (77%) responded to CRT either by improvement of NYHA functional class and/or systemic ventricular function. There were 11 non-responders to CRT. Of these, three patients died and four underwent heart transplantation. Conclusion: In this cohort of older CHD patients, CRT was accomplished with a success rate comparable to those with acquired heart disease despite the complex anatomy and technical challenges frequently encountered in this population. Further studies are needed to establish appropriate guidelines for patient selection and long term outcome.